2023
DOI: 10.3390/tropicalmed8020114
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Pneumocystis Pneumonia Infection among HIV Patients in Ethiopia: A Systematic Review

Abstract: Pneumocystis pneumonia (PCP) is a leading cause of death among patients with AIDS worldwide, but its burden is difficult to estimate in low- and middle-income countries, including Ethiopia. This systematic review aimed to estimate the pooled prevalence of PCP in Ethiopia, the second most densely populated African country. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines were used to review published and unpublished studies conducted in Ethiopia. Studies that reported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Our study included study participants who were on DTG-based as well as on EFV-based regimens which have better tolerability to enhance ART adherence and subsequent VLS than only the EFV-based regimens. However, the finding is higher than the studies conducted in eastern Ethiopia, South Africa, and Uganda [22,27,28,46]. The difference might be due to differences in study design, study subject, and operational definition for elevated viral load.…”
Section: Plos Onementioning
confidence: 58%
See 2 more Smart Citations
“…Our study included study participants who were on DTG-based as well as on EFV-based regimens which have better tolerability to enhance ART adherence and subsequent VLS than only the EFV-based regimens. However, the finding is higher than the studies conducted in eastern Ethiopia, South Africa, and Uganda [22,27,28,46]. The difference might be due to differences in study design, study subject, and operational definition for elevated viral load.…”
Section: Plos Onementioning
confidence: 58%
“…The study also showed that 29.0% versus 28.8% of women enrolled in PMTCT care newly, and 5.6% versus 7.8% of women started ART during the delivery or breastfeeding period among women in the DTG-based and in the EFV-based regimens arm respectively. The median (IQR) maternal ART duration on PMTCT care was 22 (19)(20)(21)(22)(23)(24) months for the DTG-based regimens arm and 22 (19)(20)(21)(22)(23)(24)(25) months for the EFV-based regimens arm (Table 3).…”
Section: Drug and Clinical-related Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation